The end of automobile dependence how cities are moving beyond car-based planning - Newman, Peter 1945-; Kenworthy, Jeffrey R. 1955- (Island Press, 2015)
In "The End of Automobile Dependence", Newman and Kenworthy look at how we can accelerate a planning approach to designing urban environments that can function reliably and conveniently on alternative modes, with a refined and more civilized automobile playing a very much reduced and manageable role in urban transportation. The authors examine the rise and fall of automobile dependence using updated data on 44 global cities to better understand how to facilitate and guide cities to the most productive and sustainable outcomes.
Keywords: Urban transportation policy; Urban transportation / Environmental aspects; Sustainable development; Land use, Urban; Automobiles / Environmental aspects; BUSINESS & ECONOMICS / Industries / Transportation; TRANSPORTATION / Public Transportation; Industrie; Nachhaltigkeit; Umwelt; Wirtschaft; Personenkraftwagen; Verzicht; Straßenverkehr; Verkehrsberuhigung; Mobilität; Umweltschutz; Stadt; Verkehrspolitik; Stadtplanung